1965
DOI: 10.1002/j.1551-8833.1965.tb01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Organic Contaminants by Granular‐Carbon Filtration

Abstract: The utilization of granular carbon filtration is a relatively simple and economical procedure. It is possible to adopt existing plant filters for a combination filtration‐adsorption unit process with minimum alteration, by filling them with granular carbon. This article summarizes carbon bed design criteria for the filtration‐adsorption technique as well as for adsorption alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Therefore, it is necessary to limit the amount of chemical substances that are released into the environment to as little as possible, and also to recover them as fully as possible. To remove these compounds from chemical and industrial wastewater, adsorption on activated carbon, [1][2][3][4] photochemical decomposition by ultraviolet irradiation [5][6][7][8][9][10] and aeration have usually been used. One problem with the use of activated carbon is cost.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to limit the amount of chemical substances that are released into the environment to as little as possible, and also to recover them as fully as possible. To remove these compounds from chemical and industrial wastewater, adsorption on activated carbon, [1][2][3][4] photochemical decomposition by ultraviolet irradiation [5][6][7][8][9][10] and aeration have usually been used. One problem with the use of activated carbon is cost.…”
Section: Introductionmentioning
confidence: 99%
“…This could result in a more rapid buildup of head loss than 6 for a dual-media filter with mixing at the interface.…”
Section: Sand and Coal Sizesmentioning
confidence: 99%
“…Cleasby and Baumann," Conley/ Camp," and Hager and Flentje 6 are just a few of the investigators who have reported recently on some of these modifications.…”
mentioning
confidence: 99%
“…The important role that activated carbons play in the air flow hoods used in laboratories where radioisotopes are manipulated in order to hold volatile atoms, such as the 131 I, as well the capacity of these carbons to bond substances contained in a solution (biocides, pesticides, chlorides, and so on) is well documented (Abramns et al, 1986;Hager and Flentje, 1965;Hayes, 1966;Joyce and Sukenik, 1964;Li et al, 2006;Namane and Hellal, 2006;Sabio et al, 2006).…”
Section: Introductionmentioning
confidence: 99%